Perceived Importance and Bundles of Ecosystem Services in the Yangtze River Middle Reaches Megalopolis, China - Zhang, Guanshi; Zhang, Xiu; Xie, Long; Zhang, Qi; Liu, Dongsheng; Wu, Hongjuan; Li, Sen (Frontiers in Environmental Science, 2021)
Understanding how different social groups of residents prioritize ecosystem services (ESs) is important for landscape planning that target improved human well-being to meet social expectations. In this study, a survey with 4580 residents in the Yangtze River Middle Reaches Megalopolis, central China, was conducted to assess the perceived importance of local ESs, identify their perceived coincidence (i.e., ES bundles) and reveal how the perceived ESs importance and ES bundles were associated with socio-environment factors, including demographic, environmental awareness and living environment. Our results showed that the provisioning ESs, especially water supply, had relatively higher perceived importance. There was no significant difference in perceived ESs importance and ES bundles between experts and ordinary residents, thus experts may recommend practices that meet the local residents’ wishes in YRMRM. In addition, we disclosed three bundles of perceived ESs (i.e. green environment service bundle, ecological stability service bundle, grain service bundle), which encompassed ES from different ES categories. Potential trade-off existed in different ES bundles mainly due to the divergent preferences by different residents. For example, residents with more bus services near residence tended to perceive green environment service bundle as more important, but perceive ecological stability service bundle as less important. This study adds important first-hand empirical data to the field of the public preferences of local residents for a region of high economic and ecological importance in China, which could provide more information and scientific basis for socially just and sustainable region environmental planning and management.